2019
DOI: 10.1001/jamaoncol.2019.0402
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Checkpoint Inhibitor–Induced Toxic Effects With Shared Cancer and Tissue Antigens in Non–Small Cell Lung Cancer

Abstract: IMPORTANCE Immunotherapy with checkpoint inhibitors targeting the PD-1 (programmed cell death 1) axis has brought notable progress in patients with non-small cell lung cancer (NSCLC) and other cancers. However, autoimmune toxic effects are frequent and poorly understood, making it important to understand the pathophysiologic processes of autoimmune adverse effects induced by checkpoint inhibitor therapy. OBJECTIVE To gain mechanistic insight into autoimmune skin toxic effects induced by anti-PD-1 treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
258
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(272 citation statements)
references
References 11 publications
8
258
3
3
Order By: Relevance
“…While a limited transformation is too weak in itself to provoke an effective T cell attack, the immune checkpoint blockade unleashes T cells against "altered-self" and tumors resulting in better overall survival [18]. This is consistent with the findings of Berner et al [19], in non-small cell lung cancer. They demonstrated that T cells recognize and target shared tumor and skin antigens during checkpoint inhibitor therapy resulting in autoimmune-mediated skin toxicity and tumor regression.…”
supporting
confidence: 84%
“…While a limited transformation is too weak in itself to provoke an effective T cell attack, the immune checkpoint blockade unleashes T cells against "altered-self" and tumors resulting in better overall survival [18]. This is consistent with the findings of Berner et al [19], in non-small cell lung cancer. They demonstrated that T cells recognize and target shared tumor and skin antigens during checkpoint inhibitor therapy resulting in autoimmune-mediated skin toxicity and tumor regression.…”
supporting
confidence: 84%
“…Studies have suggested that irAEs may develop through the targeting of antigens shared by normal and tumor tissue. A prospective study of autoimmune dermatologic toxicity in patients who received anti–PD‐1 therapy for NSCLC described 9 T‐cell antigens that were shared between tumor tissue and skin, suggesting that T cells targeting cancer cells may also target normal tissues with shared antigens . Similarly, a case series of ICI‐induced myocarditis found high levels of muscle‐specific antigens in tumors from 2 patients who developed myocarditis, suggesting that myocarditis may develop through T‐cell targeting of a shared antigen expressed by tumor, skeletal muscle, and heart .…”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
“…A number of recent studies has supported this hypothesis by showing favorable outcomes for patients with non-small cell lung cancer (NSCLC) and melanoma who developed various irAEs in response to immune checkpoint inhibition [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, a definite conclusion has not been drawn based on the findings from each single study, as contradictory results exist [23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%